Flow Cytometry: An Important Diagnostic Tool in Critically Ill Preterm Neonates with Suspected Sepsis - Goswami, Sneha; Gupta, Richa; Ramji, Siddarth (American Journal of Perinatology, 2020)
Objective Sepsis is a major cause of neonatal mortality. The gold standard for diagnosis is blood culture which suffers from low sensitivity and huge turn-around time. Flow cytometry has been extensively applied to malignant disorders and is an upcoming tool for diagnosis of nonmalignant disorders due to its rapidity and accuracy in detecting cells, cell products, and their functional states. The aim of this study was to investigate the utility of flow cytometric expression of neutrophil CD64, monocyte human leukocyte antigen (HLA-DR) and CD16 in diagnosis in suspected preterm neonates.Study Design In total, 100 preterm neonates with clinical signs of sepsis were enrolled in the study. Blood culture, C-reactive protein (CRP) and flow cytometry for nCD64, mHLA-DR, and mCD16 were performed. The neonates were divided into two groups: culture positive and culture negative and CRP and flow cytometric findings compared. ROC analysis was performed to determine the best cut-off for nCD64, mHLA-DR, and mCD16 values along with estimation of sensitivity, specificity, and predictive values. Probability of <0.05 was taken as significant.Results Out of the 100 enrolled neonates, 34 (34%) were culture positive. CRP was not found to be significantly different in the two groups. Expression of nCD64 (p = 0.03) was significantly upregulated in the blood culture positive cases with a cut-off mean fluorescence intensity (MFI) value = 4.72 and sensitivity of 92% and specificity of 52%. Expression of mCD16 (p = 0.02) was also upregulated in the blood culture positive cases with a cut-off MFI value = 4.9, with sensitivity of 41%, specificity of 83%.Conclusion The study concluded that nCD64 and mCD16 can be potential biomarkers for early diagnosis of neonatal sepsis with a high sensitivity and specificity.Key Points
Keywords: neonatal sepsis; flow cytometry; neutrophil CD64; monocyte CD16; monocyte HLA-DR